Risk factors of sickness absence - Gholamreza Pouryaghoub; Ramin Mehrdad; Fereshte Rafiee Samani; Fariba Mahmoodi (طب کار, 2016)
Introduction: Absenteeism is one of the challenging issues in managing human resources. Many social, economic and personal factors may affect sickness absence. We studied effects of some personal factors on sickness absence in a governmental organization.